Digital Media, Public Pressure, and Corruption Exposure: An Investigative Journalism Perspective - Haeruddin, Haeruddin; Anshar, Muhammad; Tawil, Norngainy Binti Mohd; Irnawati, Irnawati (Jurnal Kajian Jurnalisme, 2026)
Background: The development of digital media has changed how investigative journalism works, especially in uncovering corruption by public officials. Digital platforms have emerged, providing broader access to information and public participation. Purpose: This research aims to examine how digital investigative journalism contributes to uncovering corruption by analyzing the interaction between digital media, public pressure, and institutional accountability. Methods: This research uses a qualitative approach, employing a literature review and an instrumental case study of the corruption case involving Rafael Alun Trisambodo. Data were collected through the analysis of scientific literature, research reports, and digital media sources. Results: This study indicates that digital investigative journalism can accelerate evidence collection, expand data access, and strengthen the ability to set the agenda in public discourse. The integration of OSINT, AI, and big data enables journalists to discover hidden patterns and networks more efficiently, while crowd-based investigations enhance public participation in monitoring corruption. Additionally, digital media play a crucial role in transforming social events into avenues for uncovering corruption, as seen in the cases analyzed. However, challenges such as misinformation, cyber threats, ethical concerns, and disparities in digital literacy remain serious issues that can affect the credibility of the research process. Conclusion: Exposure of corruption in the digital era is shaped by the interplay among investigative journalism, social media participation, and public pressure, as seen in the case of Rafael Alun Trisambodo. The findings show that digital media can transform non-corruption events into channels for exposing corruption and institutional accountability. Implications: Investigative journalism has strengthened transparency, accountability, and democratic oversight. At the same time, it emphasizes the importance of ethical standards, verification mechanisms, and better digital literacy to ensure the sustainability and reliability of digital research practices.